Development of novel control strategy for multiple circuit, roof top bus air conditioning system in hot humid countries - Mansour, M. Khamis; Musa, Md. Nor; Wan Hassan, Mat Nawi; Saqr, Khalid M. (Elsevier, 2008)
A novel control strategy to improve energy efficiency and to enhance passengers’ thermal comfort of a new roof top bus multiple circuit air conditioning (AC) system operating on partial load conditions is presented. A novel strategy for automatic control of the AC system was developed based on numerous experimental test runs at various operating conditions, taking into account energy saving and thermal comfort without sacrificing the proper cycling rate of the system compressor. For this task, more than test runs were conducted at different set point temperatures of 21, 22 and 23 C. Fanger’s method was used to evaluate passenger thermal comfort, and the system energy consumption was also calculated. A performance comparison between that of the conventional AC system and that of the newly developed one has been conducted. The comparison revealed that the adopted control strategy introduces significant improvements in terms of thermal comfort and energy saving on various partial load conditions. Potential energy saving of up to 31.6% could be achieved. This results in a short payback period of 17 months. It was found from the economic analysis that the new system is able to save approximately 20.0% of the life cycle cost.